Clinical Morphological Changes in the Treatment of Deforming Osteoarthritis of the Knee Joint against the Background of Type 2 Diabetes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
For many еars, according to the data, the problems of diagnosis and treatment of knee-deforming osteoarthritis (DOA) in the background of type 2 diabetes mellitus are one of the insufficiently studied and underdeveloped areas of modern orthopaedic science. remains In this case, the development of guidelines for treatment methods, the choice of treatment tactics and the selection of operative interventions for these patients are drastically different compared to the knee joint DOA without accompanying diseases, and the failure to carry out the treatment procedures correctly can not only lead to the occurrence of various complications, but also causes a sharp decline in human performance and early disability.The purpose of the work: is to improve the results of treatment based on the clinical morphological approach to the treatment of DOA of the knee joint against the background of type 2 diabetes.